EDUCATIONAL MANAGEMENT (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Educational management is a dynamic and multifaceted discipline that plays a pivotal role in the effective functioning and continuous improvement of educational institutions. It encompasses the strategic planning, systematic organization, efficient direction, and meticulous control of resources and activities to achieve specific learning outcomes and enhance institutional effectiveness. This article provides an in-depth exploration of educational management, examining its core components, processes, challenges, and implications for modern education systems. Through a qualitative review of existing literature, case studies, and practical examples, the study highlights the importance of aligning institutional goals with the evolving needs of students and society. Key findings emphasize the critical role of leadership, resource optimization, stakeholder engagement, and innovative practices in fostering positive learning environments and promoting institutional growth. Despite challenges such as limited funding, leadership gaps, and resistance to change, effective educational management has the potential to address these issues and create resilient, inclusive, and future-ready systems. The article concludes by underscoring the need for adaptability, equity, and innovation in educational management to meet the demands of a rapidly changing global landscape. Future research directions include exploring the impact of emerging technologies and global crises on educational practices.